Pemodelan Regresi Robust Menggunakan Estimasi Skala Umum (GS) Dan M Umum (GM) Pada Tingkat Kemiskinan Di Provinsi Jawa Timur - Lutfiya Eka Rahmawati; Respatiwulan Respatiwulan; Sri Sulistijowati Handajani (Science and Education Journal (SICEDU), 2026)
Poverty is a global social issue that hinders human welfare and socioeconomic development. In Indonesia, poverty remains a serious and complex problem that continues to be a major challenge for national development. One of the main goals of Sustainable Development Goals (SDGs) is the elimination of all forms of poverty. Analysis of factors related to poverty levels in East Java Province was conducted in this study. The data used are sourced from the Central Statistics Agency (BPS), covering 38 districts/cities in East Java Province in 2023. The independent variables used in this study include Life Expectancy (UHH), Expected Years of Schooling (HLS), per capita expenditure, and economic growth. The data are indicated to be non-normally distributed and contain outliers, so modeling is carried out using robust regression. This study was conducted using two methods, Generalized Scaled (GS) and Generalized M (GM) by comparing the two results. The selection of the best model is based on the largest value, the lowest AIC value, and the number of outliers. The results of the study showed that the robust regression model of GM estimation was a better model with an value of 81.33%, an AIC value of 153. 2172, and one outlier.